Creativity and Emotional Intelligence in Adults: A Systematic Review and Recommendations for Future Research - Jalifi, Sebastian Yair (2025)
This systematic review aimed to summarize existing empirical studies on the relationship between creativity and emotional intelligence (EI) in adults, focusing on the assessment methods used for these constructs. Following the PRISMA guidelines (Preferred Reporting Items for Systematic Reviews and Meta-Analyses), 23 empirical articles were selected from PubMed, EBSCO, and Google Scholar databases. The most common approach for assessing creativity was through processes, while EI was often measured as a skill. Most of the reviewed studies showed a positive and significant correlation between EI and creativity. However, it was noted that using the trait approach to measure EI, especially when combined with self-report measures, consistently demonstrated inter-construct relationship. Implications of the study highlight the importance of developing emotional competencies to enhance creativity and personal success in social contexts.